Rancang Bangun Sistem Informasi Psikoedukasi Berbasis Web Cintadiri.id: Pencegahan dan Penanganan Self-harm - Arsad, Bambang Riono; Syihab, Aisyah; Faradiba, Andi Tenri (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
Self-harm is an intentional act of self injury without suicidal intent. In Indonesia, self-harm is becoming an increasingly serious problem, especially among teenagers. Previous studies and surveys conducted by institutions shows quite significant results with relatively high numbers. Considering that the causes of self-harm are quite complex, there is a need for education about self-harm and access to mental health services. Based on aforementioned researches, a web-based information system was developed which the author called Cintadiri.id. Cintadiri.id was designed and developed as an innovative and comprehensive information system to help prevent and deal with self-harm behavior in Indonesia. This system hopes to help people who are struggling with self-harm behavior get the information and resources they need to get help and recover. Cintadiri.id information system was developed using SDLC Waterfall method, supported with PHP programming language, MySQL database and Laravel framework.  Cintadiri.id provides various information and resources that can help people who are struggling with self-harm, including information about self-harm, resources and tools to help people who are struggling with self-harm behavior. It is hoped that Cintadiri.id can be a reference for the information and resources they need to get help.